(untitled) (Research, Society and Development, 2023)
The development of children’s language is a dynamic, gradual and continuous process, determined by the interaction of genetic, social and environmental factors. Objective: To evaluate the association of socioeconomic and sociocultural factors on the language development of children in a public day care center in the city of Marabá (PA). Method: This is a cross-sectional study, carried out with 62 children between 3 and 6 years old. The instruments used were the Denver II Developmental Screening Test, the Poverty Level Measurement Instrument and the Child’s Biopsychosocial Characteristics Questionnaire. For statistical analysis, Chi-square, Fisher, G Test and U Test were used, all with a significance level of 5%. In addition, Cluster Analysis was performed to create groupings in the sample. Results: Regarding the level of poverty, 56 (90.32%) of the children had a higher low income. As for Denver II, (24.20%) had delayed linguistic outcome and 13 (20.97%) risk result, thus, 28 (45.17%) were gathered in the questionable group. Eleven (57.90%) of the children who were completely abandoned by their fathers scored in the area of questionable language, along with 20 (60.60%) whose fathers worked piecework. Through the Cluster Analysis, it was verified the existence of three different groups of individuals, it was verified that the selected variables are significantly discriminant, and that the discriminant function itself is highly significant. Conclusion: Socioeconomic factors and social variables have a direct influence on children’s language development.